Planetary Health and Mental Health Nexus: Least Understood and Embraced in Policy Decisions - Manasi Kumar; Pim Cuijpers; Pushpam Kumar (Ubiquity Press, 2024)
Planetary health influences mental health and a better management of climate, biodiversity and pollution has co-benefits of improving mental health outcomes. The recognition and treatment of mental health, however, has been marginalized within environmental and climate change sciences and a greater understanding of the complex underlying processes and societal costs is required to appropriately manage and motivate policy responses. The paper provides seven recommendations underscoring that public policy developers and implementors need to be aware of the combined costs of inaction - that might accrue from neglecting mental health and environmental sciences- two areas that have been historically marginalized. Improved methodologies in conducting studies on the nature and mental health nexus are needed. The trajectories and models of adaptation and mitigation of climate change and environmental damage can be strengthened through adoption of mental and behavioral sciences approach.